2020
DOI: 10.1002/advs.202001374
|View full text |Cite
|
Sign up to set email alerts
|

A Macromolecule Reversing Antibiotic Resistance Phenotype and Repurposing Drugs as Potent Antibiotics

Abstract: In order to mitigate antibiotic resistance, a new strategy to increase antibiotic potency and reverse drug resistance is needed. Herein, the translocation mechanism of an antimicrobial guanidinium‐functionalized polycarbonate is leveraged in combination with traditional antibiotics to afford a potent treatment for drug‐resistant bacteria. Particularly, this polymer–antibiotic combination approach reverses rifampicin resistance phenotype in Acinetobacter baumannii demonstrating a 2.5 × 105‐fold reduction in min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 61 publications
(74 reference statements)
1
72
0
Order By: Relevance
“…Fluorescent dye PI was used to examine outer membrane permeability according to previously reported methods [ 48 ]. The collected bacterial cells in the logarithmic growth phase were rinsed with 0.01 M PBS buffer (pH 7.4) three times and diluted to OD600 = 0.5.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorescent dye PI was used to examine outer membrane permeability according to previously reported methods [ 48 ]. The collected bacterial cells in the logarithmic growth phase were rinsed with 0.01 M PBS buffer (pH 7.4) three times and diluted to OD600 = 0.5.…”
Section: Methodsmentioning
confidence: 99%
“…After centrifuging at 8000× g at 4 • C for 10 min, the precipitate was collected and resuspended in MHB. Then, EtBr effluent was monitored within 120 min at an excitation wavelength of 525 nm and an emission wavelength of 605 nm [44,48] A 5mL Escherichia coli ATCC25922 was cultured to the logarithmic growth stage. Bacteria were treated with the final concentration of 0.5 × MIC to 4 × MIC peptide and 0.01 M PBS (pH = 7.4) for 1 h. The bacteria were collected by centrifugation and washed with PBS.…”
Section: Efflux Pump Assaymentioning
confidence: 99%
“…7 A). Therefore, MDPs, exhibiting membrane permeability, are being considered as a class of potential antibiotics to reverse AMR 159 .
Figure 7 Combination therapy of MDPs and antibiotics.
…”
Section: Multi-drug Combination Therapymentioning
confidence: 99%
“…Pioneering studies have demonstrated a new strategy of increasing antibiotic potency and reverse drug resistance through the use of synthesized, polymer-based MDPs 92 , 159 , 162 . Cheng's group 92 reported that the radially amphiphilic polypeptide PHLG-Blm 40 could be applied as an effective adjuvant, to improve the permeation of commercial antibiotics in bacteria and enhance their antimicrobial activity.…”
Section: Multi-drug Combination Therapymentioning
confidence: 99%
“…Coadministration of the guanidinium‐functionalized polycarbonate [pEt‐20 ( MA‐5 )] at sub‐MIC concentration with different class of antibiotics like imipenem, azithromycin, gentamicin, and tetracycline resulted in a sharp reduction in the antibiotic's MIC and MBC values against MDR A. baumannii strains. [ 268 ] Moreover, pEt‐20 was able to repurpose rifampicin and auranofin (i.e., antituberculosis and antirheumatic drugs, respectively) more efficiently against Gram‐negative bacteria (Table 6 and Figure 9). The authors reported a 128‐ and 2048‐fold reduction in the MIC values of auranofin and rifampicin, respectively, in combination with pEt‐20 ( MA‐5 ) at 0.5 × MIC (sub‐MIC) concentration.…”
Section: Resensitization Of Obsolete Antibiotics By Macromolecular/polymeric Adjuvantsmentioning
confidence: 99%